2023
DOI: 10.1002/aic.18088
|View full text |Cite
|
Sign up to set email alerts
|

Embedding isolated Fe species in titania increases olefins for oxidative propane dehydrogenation

Abstract: Metal oxide-based catalysts are widely studied in oxidative propane dehydrogenation (OPDH), but they usually suffered from the low olefin activity, which is believed to be related to the active centers of metal-oxygen species. Herein, we report an effective cation-exchange strategy towards the development of TiO 2 nanosheets embedded isolated Fe species (Fe 1 TiO 2 ) as a highly-active and stable catalyst for OPDH. It exhibits an olefin yield of 38.2% at 520 C, 10.9 and 2.4 times higher than that of pure TiO 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Comparing the N 2 catalytic activity of Mo SACs to different transition metal atoms (Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Y, Zr, Nb, Mo, Tc, Ru, Rh, Pd, Ag, and Cd) anchored on a g-C 3 N 4 matrix, [216] it was shown that Mo SACs have a higher NRR capacity. In addition, transition metal oxide or sulfide-based atomic dispersion catalysts have also been widely used in traditional catalysis, for example, Professor Wang Xi's team [227] reported an effective cation-exchange strategy towards the development of TiO 2 nanosheets embedded isolated Fe species (Fe 1 -TiO 2 ) as a highly-active and stable catalyst for OPDH. It exhibits an olefin yield of 38.2 % at 520°C, 10.9 and 2.4 times higher than that of pure TiO 2 (3.5 %) and Fe 2 O 3 (15.6 %), respectively; and it shows a superior 100-h durability.…”
Section: Changing the Type Of Metal Atom In The Loadmentioning
confidence: 99%
“…Comparing the N 2 catalytic activity of Mo SACs to different transition metal atoms (Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Y, Zr, Nb, Mo, Tc, Ru, Rh, Pd, Ag, and Cd) anchored on a g-C 3 N 4 matrix, [216] it was shown that Mo SACs have a higher NRR capacity. In addition, transition metal oxide or sulfide-based atomic dispersion catalysts have also been widely used in traditional catalysis, for example, Professor Wang Xi's team [227] reported an effective cation-exchange strategy towards the development of TiO 2 nanosheets embedded isolated Fe species (Fe 1 -TiO 2 ) as a highly-active and stable catalyst for OPDH. It exhibits an olefin yield of 38.2 % at 520°C, 10.9 and 2.4 times higher than that of pure TiO 2 (3.5 %) and Fe 2 O 3 (15.6 %), respectively; and it shows a superior 100-h durability.…”
Section: Changing the Type Of Metal Atom In The Loadmentioning
confidence: 99%